Parent-Rated Severity of Illness and Anxiety Among Caregivers of Children Born with a DSD Including Ambiguous Genitalia - Sharkey, Christina M. (Horm Res Paediatr, 2018)
BACKGROUND/AIMS: Parents of children born with a disorder of sex development (DSD) often experience anxiety, but risk factors, including parental perception of the severity of their child’s DSD, have not been examined. We hypothesized that severity of illness (SOI) ratings would relate to parental anxiety, and would be higher for parents of children with a potentially life-threatening DSD (e.g., 21-hydroxylase deficiency). METHODS: Eighty-nine parents (M(age) =33.0, 56.2% mothers) of 51 children (M(age in months)=8.7) with a DSD including ambiguious genitalia were recruited from 12 specialized DSD clinics. Parents completed questionnaires prior to genitoplasty, 6-months post-genitoplasty, and 12-months post-genitoplasty (if completed). Data were analyzed with linear mixed modeling. RESULTS: Parental anxiety decreased over time, χ(2) (1)=10.14, p<.01. A positive relationship between SOI and anxiety was found, with SOI being a strong predictor of anxiety (b = 0.53, p<.01; χ(2) (1) = 5.33, p < .05). An SOI by time interaction indicated SOI had an increasing effect on anxiety over time, b=0.06, p<.05; χ(2) (1) = 6.30, p < .05. There was no diagnosis by SOI interaction. CONCLUSION: Parental anxiety decreased over time, but those with higher SOI ratings reported greater initial anxiety followed by slower resolution over time. Underlying etiology of DSD had no effect on the relationship between SOI and anxiety.